2019
DOI: 10.1080/15384101.2019.1617614
|View full text |Cite
|
Sign up to set email alerts
|

MiR-150-5p retards the progression of myocardial fibrosis by targeting EGR1

Abstract: To investigate the differential expression of microRNA-150-5p (miR-150-5p) and early growth response 1 (EGR1) in myocardial fibrosis (MF) cells, and determine the effect between miR-150-5p and EGR1 on MF. Human MF cells were generated via Trypanosoma cruzi (T. cruzi) infection, a mouse model of MF was generated via angiotensin II. The expression levels of miR-150-5p and EGR1 were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot assay. The correlation between miR-150-5p an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 27 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Notably, Egr1 transcription is activated in hypoxic and ischemic conditions in heart and in calcified heart valves [151,152]. The miR-150-5p retards the progression of myocardial fibrosis by targeting EGR1 [153].…”
Section: Egr1 Is At the Crossroad Of The Molecular Pathways Involved mentioning
confidence: 99%
“…Notably, Egr1 transcription is activated in hypoxic and ischemic conditions in heart and in calcified heart valves [151,152]. The miR-150-5p retards the progression of myocardial fibrosis by targeting EGR1 [153].…”
Section: Egr1 Is At the Crossroad Of The Molecular Pathways Involved mentioning
confidence: 99%
“… 11 The roles of miRNAs in diseases such as viral diseases, digestive system, nervous system and reproductive system are well-documented. 12 They have been involved in cardiac development and remodeling, and are closely related to various cardiovascular diseases such as myocardial fibrosis, myocardial hypertrophy and heart failure. 13 The expression level of miR-26b in patients with coronary heart disease is significantly lower than that in healthy people, and miR-26b is expected to become a marker for the diagnosis of coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on the diagnostic role of circulating miRNAs in AMI were initially based on big data analysis, but follow-up studies have also confirmed their relationship with cardiovascular disease which we will not discuss it here ( Liu W. L. et al, 2015 ; Wei L. X. et al, 2015 ; Xue et al, 2015 ; He and Huang, 2017 ; Besnier et al, 2019 ; Che et al, 2019 ; Li X. D. et al, 2019 ; Shen et al, 2019 ; Zhang et al, 2019 ). Meder et al (2011) identified two downregulated miRNAs, miR-1291 and miR-663b, among 121 miRNAs related to AMI through whole genome miRNA expression profiling.…”
Section: Circulating Mirnas Function As Diagnostic and Prognostic Biomentioning
confidence: 99%